2017
DOI: 10.1002/cpp.2080
|View full text |Cite
|
Sign up to set email alerts
|

Information order effects in clinical psychological diagnoses

Abstract: Therapists' diagnostic decisions are not influenced by pretreatment reports. Diagnostic decisions are affected by information order effects. Diagnostic accuracy of psychotherapists is debatable. High rate of misdiagnoses in case vignette with comorbid disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 70 publications
0
8
2
Order By: Relevance
“…This is in contrast to the results of a recent study that investigated the order of the presentation of psychological symptom information [30]. The authors found that the order of symptom description predicted the correctness of diagnostic decisions by clinicians; correct diagnostic decisions occurred more often when the symptom information was presented last (ie, a recency effect) [30]. In this study, memory was not an outcome of interest, as participants had access to both forms when making their ratings, and hence, recency did not have a positive effect on ratings.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This is in contrast to the results of a recent study that investigated the order of the presentation of psychological symptom information [30]. The authors found that the order of symptom description predicted the correctness of diagnostic decisions by clinicians; correct diagnostic decisions occurred more often when the symptom information was presented last (ie, a recency effect) [30]. In this study, memory was not an outcome of interest, as participants had access to both forms when making their ratings, and hence, recency did not have a positive effect on ratings.…”
Section: Discussioncontrasting
confidence: 99%
“…However, the order did not predict preference for the Revised form in study 2. This is in contrast to the results of a recent study that investigated the order of the presentation of psychological symptom information [30]. The authors found that the order of symptom description predicted the correctness of diagnostic decisions by clinicians; correct diagnostic decisions occurred more often when the symptom information was presented last (ie, a recency effect) [30].…”
Section: Discussioncontrasting
confidence: 84%
“…We attempted to control the effect of order by having the proctors randomly shuffling the images before laying them out on a table, but that order may not have been as random as we had intended. If not adequately randomised, the order may very well have had an effect on subjects' ranking of the disgusting images as it does on other study outcomes . The only way to sort that out is to both randomise and record the order or arrangement of those images and then correlate those patterns with subjects' responses.…”
Section: Discussionmentioning
confidence: 99%
“…If not adequately randomised, the order may very well have had an effect on subjects' ranking of the disgusting images as it does on other study outcomes. [39][40][41] The only way to sort that out is to both randomise and record the order or arrangement of those images and then correlate those patterns with subjects' responses.…”
Section: Discussionmentioning
confidence: 99%
“…87 In clinical research and daily practice, the use of structured diagnostic interviews is highly recommended for the assessment of mental disorders, because they ensure a systematic assessment of symptoms combined with clinicians' expert knowledge. [88][89][90][91][92][93][94][95] For the assessment of PTSD, the CAPS 96 is considered the diagnostic gold standard, 25 43 97 98 and its use is recommended by PTSD guidelines. 99 The CAPS was designed to represent a standard in terms of an interview-based diagnostic measure of PTSD.…”
Section: Discussionmentioning
confidence: 99%